Po co poetom Średniowiecze? Różewicz – Herbert – Miłosz - Regiewicz, Adam (Wydawnictwo Uniwersytetu Rzeszowskiego, 2020)
The paper attempts to describe the concept of the medieval period built by Polish poets: Tadeusz Różewicz, Zbigniew Herbert and Czesław Miłosz. The authors use this concept for the evaluation of contemporary times. The image of the Middle Ages is, on the one hand, an ethical concept abounding in references to the category of Heritage (civilisational and spiritual), and on the other hand, a dark period in which the individual and the human God become lost. The poets prefer using Enlightenment and Romantic clichés, creating a clear ideological view by means of them.
For What Purpose Do the Poets Refer to the Middle Ages? Różewicz – Herbert – Miłosz
Keywords: Tadeusz Różewicz; Czesław Miłosz; Zbigniew Herbert; medievalism; literary tradition; mediewalizm; tradycja literacka